Abnormal Spontaneous Eye Movements as Initial Presentation of Organophosphate Poisoning - Teixeira, Igor De Lima [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; Schelp, Arthur Oscar [UNESP]; Luvizutto, Gustavo Jose [UNESP]; De Lima, Fabricio Diniz [UNESP]; Bazan, Rodrigo [UNESP] (Columbia Univ Libraries, Center Digital Research & Scholarship, 2017)
Background: Atypical ocular bobbing may result from an intentional poisoning from an organophosphate compound. Phenomenology Shown: The patient exhibited conjugated, slow, arrhythmic, unpredictable eye movements in all directions, diagnosed as atypical ocular bobbing. Educational Value: This is a rare, well-documented, clinically relevant case for medical students for correct diagnosis and appropriate treatment of organophosphate intoxication.
Keywords: ocular bobbing; organophosphate; coma